5. Find the square rots of 4i.

Answers

Answer 1
Answer:

Answer:

√(4i)=2√(i)

Step-by-step explanation:

4i=4√(-1)

Applying square root

√(4i)

=\sqrt{4√(-1)}

=2\sqrt{√(-1)}

=2* -1^{(1)/(4)}

Now,

i=√(-1)\n\Rightarrow i=-1^{(1)/(2)}

\n\Rightarrow 2* -1^{(1)/(4)}=2* i^{(1)/(2)}=2√(i)

So, √(4i)=2√(i)


Related Questions

The students in Ms. Chang's class decide to order water bottles that advertise the walkathon. Hyun obtains two different quotes for the costs of the bottles. a. For each company, write an equation Hyun could use to calculate the cost for any number of bottles b. On the same set of axes, graph both equations from part (a). Which variable is the independent variable? Which is the dependent variable? C. From which company do you think the class should buy water bottles? What factors influenced your decision? d. For what number of water bottles is the cost the same for both companies? Explain.
If f(x) varies directly with x and f(x) = 2 when x = 10, then what is the value of f(x) when x = 40?a.8b.45c.200d.320
Am getting the hang of this but I still need help so may I please get help with this equation -7a+6a^2-10
What causal link can be inferred from this statement? As weather conditions change, birds migrate from one region to another for breeding.Weather changes cause birds to breed.Weather changes cause bird migration.Migrating birds cause weather changes.Breeding birds cause weather changes.Bird breeding causes bird migration.
Which are properties of rotations? Check all that apply.

Tara's player for cds the length of the cds are 45 minutes 52 minutes 38 minutes and 47 minutes if it takes her 2 minutes to change each cd how long will it take to play all four cds

Answers

To determine the amount of time she will need to play all the cd's, we add up the time in minutes.
                          45 minutes + 52 minutes + 38 minutes + 47 minutes
which is equal to 182 minutes. Then, Tara needs to shift from one cd to another for 3 times and this will take her a total of 6 minutes. Thus, the total number of minutes she will need in order to play all four cds is 188 minutes. 

Yasmin looked at the pattern 2, 16, 18, 54, and determined that the next number should be 162. What type of reasoning did she use? Question 8 options: inductive reasoning deductive reasoning algebraic reasoning direct reasoning

Answers

i think it would be inductive reasioning
good luck

A cup of coffee at 181 degrees is poured into a mug and left in a room at 66 degrees. After 6 minutes, the coffee is 139 degrees. Assume that the differential equation describing Newton's Law of Cooling is (in this case) dT/dt=k(T-66).1) What is the temperature of the coffee after 16 minutes?
2) After how many minutes will the coffee be 100 degrees?

Answers

The temperature of the coffee after 16 minutes is 134 degrees and after 1.3 minutes the coffee be 100 degrees.

What is Differential equation?

A differential equation is an equation that contains one or more functions with its derivatives.

A cup of coffee at 181 degrees is poured into a mug and left in a room at 66 degrees.

After 6 minutes, the coffee is 139 degrees.

Assume that the differential equation describing Newton's Law of Cooling is (in this case) dT/dt=k(T-66).

T=∫k(t-66)dt

=k(t²/2-66)+c

When t=0 and T=181

181=k(0-66)+c

181=-66k+c

when t=6, T=139

139=k(6²/2-66)+c

139=-48k+c

-42=-18k

Divide both sides by 18

k=7/3

139=-48×7/3+c

c=139+112=251

T=7/3(t-66)+251

The temperature of the coffee after 16 minutes

T=7/3(16-66)+251

T=7/3(-50)+251

T=134 degrees

After how many minutes will the coffee be 100 degrees

100=7/3(t-66)+251

100=7/3t-7/3(66)+251

100=7/3t-154+251

100=7/3t+97

100-97=7/3t

3=7/3t

9/7=t

1.3=t

Hence, the temperature of the coffee after 16 minutes is 134 degrees and after 1.3 minutes the coffee be 100 degrees.

To learn more on Differentiation click:

brainly.com/question/24898810

#SPJ5

Answer:

Step-by-step explanation:

(dT)/(dt) =k(t-66)\nT=\int\ {k(t-66)} \, dt=K((t^2)/(2)  -66)+c\nwhen t=0,T=181\n181=K(0-66)+c\n181=-66k+c\nwhen t=6,T=139\n139=k((6^2)/(2) -66)+c\n139=-48k+c\n181-139=-66k+48k\n-42=-18k\n7=3k\nk=(7)/(3) \n139=-48*(7)/(3) +c\nc=139+112=251\nT=(7)/(3) (t-66)+251\nnow complete the question

The area of triangle AED is 20 square meters. Find the area of parallelogram ABCD.20 square meters
52 square meters
15 square meters
104 square meters
diagram below.

Answers

I found the accompanying image of this problem. The triangle is a right triangle.

area of a right triangle = ab/2    where: a and b are the legs
based on the image: a = 5 m
20 square meters = (5m * b) /2
20 sq. m * 2 = 5m * b
40 sq. m / 5m = b
8 m = b 

So the image consists of 2 right triangles with a square in the middle.

Area of a square = a² = (8m)² = 64m²

Total area of the parallelogram = 2 right triangle * 20m² + 1 square *64m²
Total Area = 40m² + 64m²
Total area = 104m² ⇒ 104 square meters.

Solve for x
3x+1/14=2x/8

Answers

3x+(1/14)= 2x/8
24x+(4/7)=2x ( i multiplied everything by 8)
22x+4/7=0 ( i subtracted 2x to both sides)
22x= -4/7 ( i subtracted 4/7 to both sides) 
x= (-4/7)/ 22
x= -2/77
3x +  (1)/(14)  =  (2x)/(8)

First, you multiply everything by 8, so you get:
8(3x +  (1)/(14)) = 8( (2x)/(8))

Then, you develop, and you get:
24x +  (8)/(14) =  2x

You simplify (8)/(14) by dividing by 2, and you get:
24x +  (4)/(7) = 2x

Then, you put known numbers apart (numbers without x), and unknown numbers apart (numbers with x), which means you move 2x to the other part (and it become -2x), and (4)/(7) to the other part ( and it become - (4)/(7)), so you get:
24x - 2x = - (4)/(7)

you subtract and you get: 
22x = - (4)/(7) 

then, you move 22 to the other part, and since it's a multiplication, it become a division, so you get:
x = ( - (4)/(7) )/(22)

As you know, 22 =  (22)/(1), and dividing 2 fraction is equal to multiplying the first fraction by the inverse of the second fraction, so you get:
-(4)/(7) *  (1)/(22) = x

You multiply and you get:
- (4)/(154) = x

4 and 154 have a common factor which is 2, so you divide each one by 2, and you get:
-(4/2)/(154/2) = x

you divide, and you get:
-(2)/(77) = x

So, x = -(2)/(77)

Hope this Helps! :D

Write the quadratic equation in factored form. Be sure to write the entire equation.x2 - 5x - 24 = 0

Answers

ill show you 2x-5x-24=0
                          -3x-24=0
                                +24 +24
                               -3x=24
                                x=-8